COMPARATIVE ANALYSIS OF MAN POWER, PRODUCTIVITY, AND OUTPUT IN THE SHORT AND LONG CONVEYOR CONVEYOR USING MICRO MOTION (CASE STUDY: PT.EDS MANUFACTURING INDONESIA) - Marisa Dosma Sitanggang (Dinasti International Journal of Education Management And Social Science, 2020)
The thesis is compiled to analyze the ratio of man power, productivity and output between short and long conveyor conveyor. In addition to analyzing the conveyor which is better to be applied in PT. EDS Manufacturing Indonesia by using micro motions. The analysis used by researchers working maps, motion studies and calculation of standard time obtained from the data retrieval researchers with methods of micro motion (use a stop watch).The sample in this study is that there are in the final process assy namely setting. From the results, it can be calculated that for man power has the addition of 58% from 7 to 12, to the output increase from be 51.17 units and poduktivitas takttime increased 9% from 4 units to 4.41 units and 20% productivity standard time of 3.35 units to 4.2 units.